Pharmacoeconomics of synthetic therapies for multiple sclerosis. (24th July 2019) - D'Amico, Emanuele; Chisari, Clara G; Gitto, Lara; Zanghì, Aurora; Toscano, Simona; Patti, Francesco
ABSTRACT: Introduction : Recently, the economic impact of multiple sclerosis (MS), which includes both direct and indirect costs, has been increasing. While direct costs comprise health-care costs, such as the cost of pharmaceuticals, additional treatments such as physiotherapy, and medical aids, indirect costs are triggered by the productivity loss of patients and caregivers. Although new drugs for MS have changed the therapeutic scenario, they have increased the direct costs of health-care services. Areas covered : This review describes the pharmacoeconomic aspects of synthetic therapies for MS. Additionally, it discusses the economic impact of the various classes of licensed disease-modifying treatments (DMTs) for relapsing forms of MS. Expert opinion : The emerging and more expensive DMTs for MS represent a considerable challenge for health-care systems and resource consumption. Future research should focus on the long-term efficacy of DMTs and the cost of treating MS in a real-life setting. Future biological and radiological biomarkers could help stratify patients at early stages of MS, helping physicians design a personalized therapeutic approach that could have a positive impact in economic terms.